Indirect approach on human-wildlife conflict mitigation: potential local landscape based ecotourism in Margahayu, Labuhan Ratu VII - Elly Lestari Rustiati (International Journal of Ecophysiology, 2019)
Human-wildlife conflict in Way Kambas National Park is still going on with some social and economic lost. Indirect conflict mitigation through the building local landscape based ecotourism was studied in Margahayu, Labuhan Ratu VII, East Lampung. Its local people awareness play important role in supporting its local economy empowerment. Besides Rumah Konservasi, potential natural track showing plant diversity, entrance point for wild elephant to the settlement, orange plantation and natural swamp was chosen for further works. Name boards were assigned.